Colistin Resistance in Acinetobacter baumannii MDR-ZJ06 Revealed by a Multiomics Approach - Hua, Xiaoting; Liu, Lilin; Fang, Youhong; Shi, Qiucheng; Li, Xi; Chen, Qiong; Shi, Keren; Jiang, Yan; Zhou, Hua; Yu, Yunsong (Frontiers in Cellular and Infection Microbiology, 2017)
Acinetobacter baumannii has emerged as an important opportunistic pathogen due to its ability to acquire resistance to most currently available antibiotics. Colistin is often considered as the last line of therapy for infections caused by multidrug-resistant A. baumannii (MDRAB). However, colistin-resistant A. baumannii strain has recently been reported. To explore how multiple drug-resistant A. baumannii responded to colistin resistance, we compared the genomic, transcriptional and proteomic profile of A. baumannii MDR-ZJ06 to the induced colistin-resistant strain ZJ06-200P5-1. Genomic analysis showed that lpxC was inactivated by ISAba1 insertion, leading to LPS loss. Transcriptional analysis demonstrated that the colistin-resistant strain regulated its metabolism. Proteomic analysis suggested increased expression of the RND efflux pump system and down-regulation of FabZ and β-lactamase. These alterations were believed to be response to LPS loss. In summary, the lpxC mutation not only established colistin resistance but also altered global gene expression.